STUDI KASUS KETERBUKAAN INFORMASI PUBLIK DINAS KOMUNIKASI DAN INFORMASI KAB. MOJOKERTO DALAM TINJAUAN KOMUNIKASI PUBLIK DI MASA PANDEMI COVID-19 - Alkhakim, Ahmad Yusuf (The Commercium, 2023)
Covid - 19 is one of the most common man-made catastrophes. As a result, individuals' everyday lives as social beings tend to adapt to the current situations. The pattern of face-to-face contact that we frequently practice alters and has a significant influence on several parts of life. Similarly, reacting to the process of operating the wheels of government necessitates a considerable strategy, particularly in terms of public communication to audiences. Because communication is an abstract concept with various meanings in its application, it must encompass every attitude that offers meaning to the recipient. As a result, the disclosure of information that must be carried out by government agencies, particularly the Office of Communication and Information, must have a substantial influence on people's behavior.